Performance studies on application of transputer system in image processing - Woon, Fiona Wai Teng. (2009)
Parallel programs are characterised by their speedup behaviour. Each parallel program is a collection of many co-operating tasks and, by distributing the tasks to different processors, the parallel program can experience significant speedup. Generally, as more processors are allocated to a given parallel program, the faster the program will execute. However, there is often a point of diminishing returns, beyond which extra allocated processors are not effectively used. Extra processors would be better utilised by allocating them to another program. Thus, given a set of processors in a multiprocessor system, and a set of parallel programs, a partitioning problem naturally arises which seeks to allocate processors to programs optimally.